The synthesis and surface properties of newly eco-resin based coconut oil for superhydrophobic coating - Marsi, Noraini; Mohd Rus, Anika Zafiah; Ibrahim, Mohd Razali; Samsuddin, Syahir Arif; Abdul Rashid, Azrin Hani (Trans Tech Publications, 2017)
The paper presents the synthesis of newly eco-resin based on coconut oil for superhydrophobic coating. Superhydrophobicity of the coating provide a self-cleaning or water-repellent characteristic that prevents peeling, thereby extend the life expectancy of the coating. The use of newly synthesized eco-resin offer a sustainable, eco-friendly and cost effective source of nature. The synthesis and formulation of different percentages of coconut oil which is 20, 40, 60 and 80 weight by weight percentage (wt/wt%) consists of three phases to form superhydrophobic coating. The first phase involved alcoholysis step, condensation step and third phase purification through alcoholysis. The adhesion test (ASTM D3359-03) results was obtained the highest classification grading of 5B for coating at 80% (wt/wt) of coconut oil with 9 layer whereas the rate of adhesion is 9.87% of the area affected. It is shows that the small flakes of coating are detached at intersections. Scratch resistance test was evaluated in terms of pencil hardness grade, which is increased from grade HB to 6H and there is minor scratch occurs for 9 layer coating. The water droplet test was demonstrated that the advancing water contact angle up to 60% of coconut oil at 169.22º with the smooth surface roughness at 0.2448 µm.